Legal Assistance for the Community in Drafting Legally Valid Deeds and Agreements - salim; Junaidi Lubis; Irma Herliza Rizki; Juliya Maria (Outline Journal of Community Development, 2024)
This activity uses a qualitative approach with empirical studies to analyze the problems faced by the community in preparing deeds and agreements and to evaluate the effectiveness of the legal assistance program provided. Data were collected through interviews, observations, and documentation studies. The results of the study indicate that the majority of the community has a limited understanding of the requirements for the validity of an agreement and the differences between authentic deeds and private deeds. Legal assistance carried out through education and consultation has been proven to increase community understanding and change the pattern of preparing agreements to be more in accordance with legal provisions. However, challenges such as limited legal personnel and access to services are still major obstacles. To increase the effectiveness of this program, it is recommended to establish a community-based legal service center and utilize digital technology for legal consultations. Thus, it is hoped that legal assistance can increase public awareness and access to better quality legal services.